A systematic study of North American Angelica species (Apiaceae) based on nrDNA ITS and cpDNA sequences and fruit morphology. Issue 4 (12th February 2021) - Liao, Chen‐Yang; Gao, Qing; Katz‐Downie, Deborah S.; Downie, Stephen R.
Abstract: Angelica is a taxonomically complex genus widespread throughout the North Temperate Zone. Previous phylogenetic studies of the genus have focused primarily on its East Asian species. The relationships among its North American members, the monophyly of these species, and the value of fruit morphology in circumscribing its taxa have yet to be examined. This study represents the most comprehensive sampling of Angelica to date (100 species) and includes all 26 species in North America. Relationships are inferred using Bayesian inference, maximum likelihood, and maximum parsimony analyses of ITS sequences and, for multiple accessions of each North American species, cpDNA ndhF‐rpl32, rpl32‐trnL, and psbM‐psbD sequences. The fruit morphological characters examined were those considered phylogenetically important in East Asian Angelica . The results revealed that the North American species fell into three major clades: North American Angelica clade, Archangelica clade, and the Eurasian Angelica clade. Angelica dawsonii has affinities with Lomatium brandegeei . Fourteen species within the North American Angelica clade were strongly supported as monophyletic. Two paraphyletic species resulted in new combinations in A. lineariloba and A. venenosa . Conflict between the ITS‐derived and cpDNA‐derived phylogenies and the lack of resolution in portions of the trees may be due to chloroplast capture and rapid species radiation. Fruit morphology supported some interspecific relationships based on molecular data, and relationships revealed by ITS and cpDNA data were roughly in accordance with fruit classification type and geographic distribution region, respectively. A diagnostic key based on fruit morphology is provided for the identification of the North American Angelica taxa. Abstract : The North American Angelica clade includes 26 species, of which 14 are monophyletic. Two paraphyletic species resulted in new combinations in A. lineariloba and A. venenosa . Relationships revealed by ITS and cpDNA data are roughly in accordance with fruit classification type and geographic distribution region, respectively.